Political everyday life of Mariupol Ukrainians in the revolutionary processes of 1917 on the material of periodicals - Volodymyr Romantsov; Natalia Romantsova (Cхід, 2020)
The article highlights the issue of political everyday life of Mariupol Ukrainians in the revolutionary processes of 1917 on the basis of the analysis of periodicals. The informational and organizing role of the regional periodicals of that time, that, along with other aspects, contained reports on the political situation in Ukraine, the activities of Mariupol Ukrainians and the political influence on them by the Ukrainian Central Rada, have been emphasized. An analysis of the political everyday life of Mariupol Ukrainians in the revolutionary processes of 1917 makes it possible to determine the peculiarities of this social phenomenon. The change of vectors of everyday life of Mariupol Ukrainians in the political sphere during 1917 under the influence of revolutionary processes have been traced. It has been proved that the political everyday life of Mariupol Ukrainians in the rapid events of the revolution was determined by the influence of several factors: the Ukrainian Revolution, which began in 1917 as part of the Russian democratic revolution and after the adoption of the Third Universal, received a national character; the struggle for the revival of Ukrainian statehood, which was legally documented by the Universals of the Central Rada; active formation of Ukrainian identity at the regional level, social attitude in Ukraine in general and the Northern Azov and Mariupol; worsening of social contradictions and intensification of military and political confrontation at the end of the year. The place of activists of the Ukrainian movement in Mariupol in the political life of the revolutionary period has been defined.